Synthesis, Modification And Characterization Of Layered Hydroxides And Magnetite And Their Nanohybrids With D-Gluconate And Gallate Anions - Ghotbi, Mohammad Yeganeh (2009)
Formation of organic-inorganic nanohybrid material of D-gluconate in the lamellae of zinc-aluminum-layered double hydroxide was accomplished by both spontaneous self-assembly (direct method) and ion-exchange methods. PXRD together with CHNS and FTIR analyses showed that the hybridization of D-gluconate with pure phase and good crystallinity was successfully accomplished using both direct and indirect methods. This work showed that a food additive, such as D-gluconate can be hybridized into an inorganic host for the formation of a new nanohybrid compound which can be used to regulate the release of acidity in the food industry. A new organo-mineral nanohybrid material, in which the organic moiety was hybridized into the inorganic interlamellae, was prepared using gallate anion (GA), an anti-carcinogenic, anti-mutagenic, and anti-microbial agent as a guest, and Zn-Al-layered double hydroxide, as an inorganic layered host using the ion-exchange technique. The release of the anion from the interlamellae of the nanohybrid was found to be of controlled manner, governed by the first order kinetic and it was also concentration-dependent. Zinc hydroxide nitrate, a brucite-like layered material, was synthesized using pH controlled method. Poly (vinyl alcohol) and poly (ethylene glycol) were used at various percentages as size decreasing agents during the synthesis of zinc layered hydroxide. SEM images, PXRD, TGA and surface area analyses showed the decrease of size and thickness of the resultant zinc layered hydroxides. When zinc layered hydroxides were heat-treated at 500 °C, the sizes of obtained nano zinc oxides were depended on the size of the parent material, zinc layered hydroxide nitrate. The memory effect of calcined zinc layered hydroxide nitrate, with gallate anion solutions, was studied. The brucite-like material, zinc layered hydroxide nitrate was heat-treated at 150-800 ºC. XRD analysis showed the growth of the calcined materials, nano sized zinc oxides in both thickness and diameter occurring simultaneously with increasing calcination temperature. The rehydration behavior of the calcined material was investigated by placing the material in a solution containing gallate anions. The best result for brucite-like phase reconstruction was obtained for a sample heated at 500 ºC and treated with 0.1 M anion. XRD analysis showed the formation of a layered structure material after rehydration process. Brucite-like materials, undoped and doped zinc layered hydroxide nitrate with (2 % molar in mother liquor) Fe3+, Co2+ and Ni2+ were synthesized. Their organic-inorganic nanohybrid materials with gallate anion as a guest, and the undoped and doped zinc hydroxide materials,as inorganic layered hosts, were prepared by the ion-exchange method. The nanohybrid materials were heat-treated at various temperatures, 400-700 ºC. XRD, TGA/DTG and FTIR results showed that incorporation of the doping agents within the zinc layered hydroxide has enhanced thermal stability of the nanohybrid materials in the thermal decomposition pathway. FESEM images have illustrated porous carbon materials obtained from the heating of the nanohybrids at 600 and 700 ºC after the acid washing process. Magnetite nanoparticles with narrow size distribution was prepared by using poly (vinyl pyrrolidone) as a stabilizing agent during the synthesis. Immobilization of gallate anion (GA), onto the surface of magnetite nanoparticles was accomplished by adsorption technique that was found to be efficient for the hybridization process in the formation of the core-shell nanohybrid. FTIR and CHNS results indicated that the GA was actually adsorbed onto the surface of the magnetite nanoparticles. Also, size analysis showed successive size increases of the particles after the adsorption process. The release of the anion from the surface of the nanohybrid was found to be controllable by the selection of the release media. This study showed that the formation of organic-inorganic nanohybrid materials of D-gluconate and gallate anions as organic guests and zinc-aluminum-layered double hydroxide, zinc layered hydroxide nitrate and also magnetite nanoparticles as hosts can be successfully accomplished.